Branched Antisense and siRNA Co‐Assembled Nanoplatform for Combined Gene Silencing and Tumor Therapy. (24th November 2020) - Liu, Jianbing; Lu, Xuehe; Wu, Tiantian; Wu, Xiaohui; Han, Lin; Ding, Baoquan
Abstract: Chemically modified DNA has been widely developed to fabricate various nucleic acid nanostructures for biomedical applications. Herein, we report a facile strategy for construction of branched antisense DNA and small interfering RNA (siRNA) co‐assembled nanoplatform for combined gene silencing in vitro and in vivo. In our design, the branched antisense can efficiently capture siRNA with 3′ overhangs through DNA–RNA hybridization. After being equipped with an active targeting group and an endosomal escape peptide by host–guest interaction, the tailored nucleic acid nanostructure functions efficiently as both delivery carrier and therapeutic cargo, which is released by endogenous RNase H digestion. The multifunctional nucleic acid nanosystem elicits an efficient inhibition of tumor growth based on the combined gene silencing of the tumor‐associated gene polo‐like kinase 1 (PLK1). This biocompatible nucleic acid nanoplatform presents a new strategy for the development of gene therapy. Abstract : A nucleic acid nanoplatform‐based co‐delivery system containing a pair of functionalized branched antisenses and siRNA with 3′ overhangs was constructed through controlled co‐assembly for combined gene silencing and tumor therapy in vivo.